Homologous proteins SAPCD2X1 and SAPCD2 have significantly different carcinogenic capacities in human colorectal cancer cells based on structural prediction and functional verification: Expression and biological functions of the SAPCD2X1 protein - Li, Jingchun; Chen, Yuan; Wang, Xiaolong; He, Wenxi; Liu, Chunli; Feng, Feng; Zhang, Wenwei; Cao, Hongtao; Long, Qixiong; Gao, Fang; Sun, Wei (Cellular and Molecular Biology, 2023)
We discussed the expression and biological functions of the SAPCD2X1 protein in the HCT116 CRC cell line by bioinformatics analysis and prediction, and biological function verification. Spatial conformation models of SAPCD2X1 and SAPCD2 were predicted using the threading method, ensemble method, and several other protein structure prediction approaches. The conformational similarity between SAPCD2X1 and SAPCD2 was studied, and their functions were predicted. The biological experiments showed that SAPCD2X1 and SAPCD2 were overexpressed in CRC cells. SAPCD2X1-specific antibodies were prepared. The expressions of SAPCD2X1 and SAPCD2 were localized in cells using the immunofluorescence assay. The SAPCD2 and SAPCD2X1 overexpression models were validated using Western Blot and RT-qPCR. We successfully predicted the structures of the SAPCD2X1 and SAPCD2 proteins, and visualized them using the VDM software. It was predicted that the tertiary structure of SAPCD2X1 changed significantly compared with SAPCD2. Alteration of the biological functions of SAPCD2X1 was also predicted due to the changes in the spatial conformation of the protein. Anti-SAPCD2X1 antibody and SAPCD2X1-EGFP and SAPCD2-EGFP recombinant plasmids were established. The overexpression of the two proteins was induced in HCT116 cells using the recombinant plasmids, and verified by RT-qPCR and Western Blot. Meanwhile, the anti-SAPCD2X1 antibody was proved to have a high specificity. The immunofluorescence assay showed that SAPCD2X1 and SAPCD2 are mainly expressed in the cytoplasm. SAPCD2X1 and SAPCD2 exhibited significantly different biological functions in HCT116 cells. SAPCD2 is a carcinogenic protein, while SAPCD2X1 does not affect the proliferation, invasion, and migration of human CRC HCT116 cells.